RETRACTED: Optimizing sgRNA to Improve CRISPR/Cas9 Knockout Efficiency: Special Focus on Human and Animal Cell - Shojaei Baghini, Sadegh; Gardanova, Zhanna R.; Zekiy, Angelina Olegovna; Shomali, Navid; Tosan, Foad; Jarahian, Mostafa (Frontiers in Bioengineering and Biotechnology, 2021)
During recent years, clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) technologies have been noticed as a rapidly evolving tool to deliver a possibility for modifying target sequence expression and function. The CRISPR/Cas9 tool is currently being used to treat a myriad of human disorders, ranging from genetic diseases and infections to cancers. Preliminary reports have shown that CRISPR technology could result in valued consequences for the treatment of Duchenne muscular dystrophy (DMD), cystic fibrosis (CF), β-thalassemia, Huntington’s diseases (HD), etc. Nonetheless, high rates of off-target effects may hinder its application in clinics. Thereby, recent studies have focused on the finding of the novel strategies to ameliorate these off-target effects, and thereby lead to a high rate of fidelity and accuracy in human, animals, prokaryotes and also plants. Meanwhile, there is clear evidence indicating that the design of the specific sgRNA with high efficiency is of paramount importance. Correspondingly, elucidation of the principal parameters contributed to determining the sgRNAs efficiencies is a prerequisite. Herein, we will deliver an overview regarding the therapeutic application of CRISPR technology to treat human disorders. More importantly, we will discuss the potent influential parameters (e.g., sgRNA structure and feature) implicated in affecting the sgRNA efficacy in CRISPR/Cas9 technology, with special concentration on human and animal studies.